2019
DOI: 10.18805/ijare.a-435
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Phosphorus Fertilizers Application on Phosphorus use Efficiency and Grain Protein of Winter Wheat in Alkaline-Calcareous Soil, Southern Algeria

Abstract: hree field experiments (2008 to 2011) were conducted to evaluate the ability of winter wheat (Triticum durum Desf. var. Carioca) to utilize and acquire soil phosphorus and nitrogen under different sources of phosphate fertilizers (Fosfactyl, Single super phosphate and Mono-ammonium-phosphate) and rates of applications (30, 60, 90 and 120 kg Pha-1) with a fixed level of nitrogen fertilization. Results revealed a significant effect of P rates on phosphorus use efficiency (PUE) and nitrogen use efficiency (NUE); … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…This finding indicates that neither the form of P carrier nor the dose of P played a significant role in the development of these grain quality characteristics. The studies by Gaj et al [62] and Boukhalfa-Deraoui et al [63] found no significant difference in grain protein content as a function of P source used. Similarly, Wołoszyk et al [64] observed no effect of different waste-derived soil amendments on test weight, protein content, and Zeleny test.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…This finding indicates that neither the form of P carrier nor the dose of P played a significant role in the development of these grain quality characteristics. The studies by Gaj et al [62] and Boukhalfa-Deraoui et al [63] found no significant difference in grain protein content as a function of P source used. Similarly, Wołoszyk et al [64] observed no effect of different waste-derived soil amendments on test weight, protein content, and Zeleny test.…”
Section: Discussionmentioning
confidence: 90%
“…The lack of response of technological properties of the grain, particularly protein, gluten, and starch content, to an increase in P dosage may be explained by the findings of Agapie and Bostan [66], which suggest that unilaterally applied P does not significantly affect the studied qualitative parameters, but is used as a support for N. Furthermore, the results of the present study are consistent with the findings of Eppendorfer [67] that P affects the amino acid composition of wheat grain only indirectly through its effects on N concentration. Boukhalfa-Deraoui et al [63] reported that the P application rates (30, 60, 90 and 120 kg P ha −1 ) were not significant for the protein content of the wheat grain when the N fertilization level was fixed. In the present study, the N rate was the same for all plots within each experiment, including those with no P treatments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation